(untitled) (TUTA Journal, 2024)
Effectiveness of teaching speaking through audio aids plays principal role in scaffolding speech communication verbally in the classroom, such as selection and use of language as a resource as well as medium of instruction, instructional strategies and teaching materials. Considering classroom space as a social space, this paper explores whether or not linguistic discourse analysis can be used as a resource for learning, the effectiveness regarding the use of audio aids as a resource in second/foreign language classroom management. The information for this phenomenological qualitative research study in a constituent campus through a series of interviews of the students reveals by the researcher, classroom observation and informal interactions of the students to raise the issues. From this study it is concluded that ample opportunities should be given to use audio aids as the medium of instruction in the classroom settings creating face to face interaction, speech conversation, debate and live dialogue in order to tap the students’ communicational talents and abilities for developing constituent campus